Does it pay to concentrate conservation efforts for dead‐wood dependent insects close to existing reserves: a test on conservation planning in Sweden. Issue 4 (5th December 2017) - Hallinger, Martin; Kärvemo, Simon; Ranius, Thomas
Abstract: Forestry has significantly changed many boreal forest landscapes with negative effects on biodiversity. Main reasons are habitat loss and deterioration, due to a simplified forest composition, including a reduction in old trees and dead wood. In Sweden, measures to counter the loss of biodiversity are taken at forest harvesting, and include forest harvest retention. Areas of high conservation values (AHCV) have been identified in Sweden to prioritise conservation efforts, but so far these areas have not been used when making decisions about forest harvest retention. In this study, we tested if dead wood from forest harvest retention is used by more dead wood‐dependent insect species (24 beetles and four other insects, redlisted or indicating high biodiversity) on clearcuts within than outside of AHCVs and whether the composition of the surrounding landscape influences species occurrence. There were not more dead wood‐dependent insect species per clearcut within AHCVs than outside. The surrounding landscape had an influence on the species richness on clearcuts, but in several cases the pattern was the opposite of our hypotheses. Increased standing volume of relevant tree species, however, tended to increase the occurrence or number of associated species. The designation of ACHVs in Sweden is not related with occurrence of dead wood or dead wood‐dependent organisms. We also found that landscape context can have effects on species richness. The result urges for better planning so that ACHV areas are designated in landscapes where their potential for conservation of dead wood‐dependent organisms is highest.